Rock Brands: Selling Sound in a Media Saturated Culture - Christian, Elizabeth Barfoot (Lexington Books, 2010)
Rock Brands: Selling Sound in a Media Saturated Culture, edited by Elizabeth Barfoot Christian, is an edited collection that explores how different genres of popular music are branded and marketed today. The book's core objectives are addressed over three sections. In the first part of Rock Brands, the authors examine how established mainstream artists/bands are continuing to market themselves in an ever-changing technological world, and how bands can use integrated marketing communication to effectively 'brand' themselves. This branding is intended as a protection so that technology and delivery changes don't stifle the bands' success. KISS, AC/DC, Ozzy Osbourne, Phish, and Miley Cyrus are all popular musical influences considered in this part of the analysis. In the second section, the authors explore how some musicians effectively use attention-grabbing issues such as politics (for example, Kanye West and countless country musicians) and religion (such as with Christian heavy metal bands and Bon Jovi) in their lyrics, and also how imagery is utilized by artists such as Marilyn Manson to gain a fan base. Finally, the book will explore specific changes in the media available to market music today (see M.I.A. and her use of new media) and, similarly, how these resources can benefit music icons even after they are long gone, as with Elvis and Michael Jackson. Rock Brands further examines gaming, reality television, and social networking sites as new outlets for marketing and otherwise experiencing popular music. What makes some bands stand out and succeed when so many fail? How does one find a niche that isn't just kitsch and can stand the test of time, allowing the musician to grow as an artist as well as grow a substantial fan base? Elizabeth Barfoot Christian and the book's contributors expertly navigate these questions and more in Rock Brands: Selling Sound in a Media Saturated Culture.